Openness–growth nexus in Pakistan: a macro–econometric analysis - Zakaria, Muhammad; Ahmed, Eatzaz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
The paper empirically examines the effects of trade openness policy on economic growth in Pakistan using various channel variables. Quarterly data is used for the period 1981/82 to 2007/08. The results of GMM estimates indicate that there are ten broad pathways through which trade openness policy has an indirect effect on growth. Trade openness policy positively affects growth through its impact on physical capital, human capital, foreign investment, inflation, real exchange rate, foreign debt, corruption and foreign exchange market distortions, while it negatively affects growth through government consumption and democracy. The results also indicate that the positive effects outweigh the negative ones, thereby delivering the overall positive effect of trade openness policy on output growth. This effect is economically reasonable and statistically significant. This result is robust to alternative estimation techniques, equation specifications and the inclusion of some other channel variables
Argumenta Oeconomica, 2013, Nr 1 (30), s. 47-84
Keywords: trade openness; output growth; Pakistan; wzrost gospodarczy; polityka handlowa